Endothelin: an important factor in acute renal failure? - Firth, J; Ratcliffe, P; Raine, A; Ledingham, J (1988)
Very low concentrations of the vasoconstrictor peptide endothelin cause intense long-lasting renal vasoconstriction. In the isolated perfused rat kidney, the concentration of endothelin required to reduce blood-flow by 50% is 200 pmol/l, compared with 1000 pmol/l angiotensin II (previously the most potent known vasoconstrictor). Whereas angiotensin II has little effect on the glomerular filtration rate (GFR), a rise in endothelin from 100 to 800 pmol/l reduces GFR by 90%. Endothelin is probably present in the circulation at low concentrations in vivo; events associated clinically with acute renal failure would tend to increase this concentration. Endothelin may be a mediator in the pathogenesis of acute renal failure.